Answer:
n=8
Step-by-step explanation:
n/2+3=7
-3 -3
n/2 = 4
*2 *2
n=8
The answer of 4(2x^3 y^4 )^4/2(2x^2 y^6 )^3 after simplification will be
4
Step-by-step explanation:
To simplify
.
Using exponential law the exponents of variables will be added when multiplied as per rule
we get
Now by dividing according to exponential rule the exponents of variables will be subtracted as per rule
So the answer of 4(2x^3 y^4 )^4/2(2x^2 y^6 )^3 after simplification will be
4
Keywords: Algebra
Learn more about algebra at:
#learnwithBrainly
Answer:
$33.60 would be the total cost